The Jurisprudence of Direction for Use in Product Liability: Issues in Perspectives - Akinrinmade, Gbade (European Journal of Sustainable Development, 2017)
A product no matter how safely made, has the potential danger of injuring human life. It is therefore mandatory to call the attention of users to potential dangers or defects inherent in such products or how best such product may be used. The absence of warning or directions for use may also render an otherwise acceptably safe product unsafe. This therefore makes it imperative that products be accompanied with adequate warning instruction or instruction for use. Bearing in mind that the essence of warning is to call the attention of consumers to defects associated with the use of a product, whilst that of instruction for use is to ensure safety on how best the product can be put to use; it is unfortunate that such warnings or instructions for use fail to achieve the desired purpose. The reason being that such warnings or instructions are either couched in a language that most of the users are not literate about or its wordings are not legible / wrongly placed on the product's package. These shortcomings has led to product injury/accident and at times loss of lives as a result of such shortcomings. It is in the light of the above that this paper ex-ray the role of warning in product liability; and also justify the need why warnings and instructions connected with the usage of products should be couched in the language understood and spoken by the majority of people where such product is been offered for sale in order to ensure the safety of human lives. The fact is incontrovertible that defective or unsafe product has grave consequences on sustainability of the society. Keywords: Use Direction Product Liabilty, Sustainability